A comprehensive phylogeny of extinct and extant Rhizomyinae (Rodentia): evidence for multiple intercontinental dispersals. (24th October 2012) - López‐Antoñanzas, Raquel; Flynn, Lawrence J.; Knoll, Fabien
Abstract The subfamily Rhizomyinae is known from the Late Oligocene up to the present. Today this group comprises six species, which live in southern Asia and eastern Africa. Despite the current moderate diversity of the rhizomyines, they had a greater diversification and wider distribution in the past: from Asia, their land of origin, to Africa, which they entered during the Early Miocene. So far 33 fossil species can be referred to this group. A cladistic analysis involving fossil and living species has been carried out. Prokanisamys spp. turned out to be the most basal taxa of the ingroup. This analysis calls into question the monophyly of several genera, and allows the proposal of a phylogenetic definition of the tribes Tachyoryctini and Rhizomyini. It also provides information about the origin of the African rhizomyines and allows inferring multiple dispersal phenomena from Asia to Africa in Early and Late Miocene times.